Исследование количества и распределения эфиромасличных железок на листьях некоторых видов рода Ocimum L - Кустова, О.К. (Промышленная ботаника, 2004)
Quantitative characteristics and regularities of ether-bearing glandules distribution on the surface of O. basilicum, O. sanctum and O. gratissimum leaves have been determined. The largest number of ether-bearing glandules is concentrated in basal part of leaves of the investigated specimens of O. basilicum and O. sanctum, and in medial part – of O. gratissimum. The increment of leaf parameters did not presuppose significant increase of ether-bearing glandules number. The largest value of the total number of ether-bearing glandules of the leaves among the studied species of Ocimum has been determined for O. gratissimum. Glandules density on the formed leaf is confirmed by data published for Lamiaceae Lindl. species.